2015
DOI: 10.1186/s12985-015-0439-5
|View full text |Cite
|
Sign up to set email alerts
|

MERS coronavirus: diagnostics, epidemiology and transmission

Abstract: The first known cases of Middle East respiratory syndrome (MERS), associated with infection by a novel coronavirus (CoV), occurred in 2012 in Jordan but were reported retrospectively. The case first to be publicly reported was from Jeddah, in the Kingdom of Saudi Arabia (KSA). Since then, MERS-CoV sequences have been found in a bat and in many dromedary camels (DC). MERS-CoV is enzootic in DC across the Arabian Peninsula and in parts of Africa, causing mild upper respiratory tract illness in its camel reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
341
0
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(368 citation statements)
references
References 158 publications
7
341
0
20
Order By: Relevance
“…A study from Saudi Arabia showed that more than 50% of Saudi people older than 50 years have diabetes [43]. However, in the studies by Assiri et al, [12] and Mackay et al, [13] the large number of people with MERS-CoV infection and chronic disease might have been due to the hospital outbreak where patients were first admitted. Our results are inline with a recent case-control study where previous medical conditions such as diabetes mellitus, heart disease, and smoking, were each independently associated with MERS-CoV disease [14].…”
Section: Discussionmentioning
confidence: 97%
“…A study from Saudi Arabia showed that more than 50% of Saudi people older than 50 years have diabetes [43]. However, in the studies by Assiri et al, [12] and Mackay et al, [13] the large number of people with MERS-CoV infection and chronic disease might have been due to the hospital outbreak where patients were first admitted. Our results are inline with a recent case-control study where previous medical conditions such as diabetes mellitus, heart disease, and smoking, were each independently associated with MERS-CoV disease [14].…”
Section: Discussionmentioning
confidence: 97%
“…The transmission of MERS-CoV is defined as sporadic between family members, often occur in health care settings, and requiring close and prolonged contact [6]. The Coronavirus infection was initially thought to spread by zoonotic events via bats.…”
Section: Introductionmentioning
confidence: 99%
“…MERS‐CoV has infected more than 1700 humans, with 30% to 40% mortality rate, mainly in countries of the Arabian Peninsula . Dromedary camels are strongly believed to be an intermediate host and an important source of infection although the exact transmission mechanism is still unclear . Human‐to‐human transmission has been documented, although this requires a very close and lengthy contact with patients .…”
Section: Introductionmentioning
confidence: 99%